Origins, Legal Regulations and Structure of the Atomic Energy Authority (1973-1976). A Historical and Legal Overview of the Subject - Dąbrowski, Przemysław (PRAWO i WIĘŹ, 2025)
The UEA existed for less than three years. Thanks to the changes introduced, there was a significant development in the creation of conditions for the peaceful use of atomic energy, and the social and economic development of the Polish state was accelerated. The Office was abolished on 27 March 1976, when the Office of the Minister of Energy and Atomic Energy was established.